Journalism's martyrs: profiles of reporters and others murdered in the line of duty - Weeks, Andrew (McFarland & Company, Inc., Publishers, 2022)
"Journalists have often put themselves in danger to convey crucial information to the public. Many journalists have even died while doing their jobs, whether investigating crimes or traveling to battle zones--and sometimes documenting events in their own communities. Recently, reporters have been assaulted, mocked and silenced, dubbed "fake news" and "enemy of the people." Despite its flaws, the free press is one of the country's most reliable foundations for ensuring a free and fair democracy for current and future generations. This book tackles some of the most important issues affecting today's reporters and newsrooms through profiling journalists killed on the job, whether from violent conspiracy, terrorism or mass shootings. Although this book aims to focus on American journalism, a short chapter is devoted to the Saudi Arabian journalist Jamal Khashoggi. The profiles in this book contextualize the deaths of these journalists within an ever-evolving public perception of the Fourth Estate"--